Al-Qur'an sebagai Sumber Sejarah - M. Dahlan M (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2009)
Al-Qur'an constitutes an acurate historical source. Its historical exploration is supported by factual and true story. By this method, the data existing in al-Qur'an are easily remembered and well understood for its story was uttered repeatedly in a same verse in different chapters. Al-Quran is objectively serving the readers the past events, for it contains the miracle and the incomparable essence. On the other hands, al-Qur'an, as it is a holy book, also becomes the main reference of history for anyone who concerns with the historical resources.